PPG Goes to Bulungan: Numeracy, Joyful Learning, Design Thinking and Learning Media Workshop for Elementary and Junior High School Teachers - Wulandari, Shinta; Darmayasa, Jero B; Hamid, Hariaty; Anwar, Azwar; Winarno, Winarno; Tanjung, Firima Zona; Apriliyana, Nur Pangesti (Jurnal Pengabdian Sains dan Humaniora, 2025)
PPG Goes to Bulungan is a community service program aiming to strengthen the capacity of elementary and junior high school teachers in Bulungan Regency in designing lessons that foster students' numeracy skills, joyful learning environments, application of design thinking principles, and utilization of innovative learning media. This initiative responds to the national urgency of improving the quality of basic education as aligned with the Merdeka Curriculum and regulations from the Minister of Education, Culture, Research, and Technology regarding graduate and process standards. The program was implemented through participatory and collaborative workshops combining theory and hands-on practice. Results revealed increased teacher understanding of numeracy concepts and joyful learning, enhanced ability to apply design thinking to educational challenges, and improved skill in developing interactive media. This activity positively impacted teachers' professional competence and contributed to educational transformation in remote areas.